Production & characterization of multi-walled carbon nanotube (carboxyl -functionalized) reinforced polyesters - Prakash, Jeganmohan (2014)
This paper presents the study on the production and characterization of Carbooxyl functionalized Multi-Walled Carbon Nanotube (MWCNT) reinforced Polyester composite. The main objective of this study is to optimize the weight percentage of MWCNT in the composite and to optimize the sonication time of the composite. To determine the optimum weight percentage of MWCNT, samples with different weight percentage of MWCNT was prepared. The prepared samples were sonicated for one hour and were tested for its viscosity. From the result, the viscosity was the highest at 0.4wt % MWCNT. Hence, the optimum weight percentage of MWCNT is at 0.4wt % MWCNT. After optimizing the weight percentage of MWCNT, the sonication time was optimized. This was done by preparing samples of 0.4wt % MWCNT which was then sonicated at different time intervals. After sonication, the viscosity was determined. From the result, the viscosity was the highest for the sample that was sonicated for 90 minutes. Hence, the optimum sonication time of 0.4wt % MWCNT is 90 minutes. After optimization, the composite was then characterized using Tensile Strength (TS) test, Thermal Gravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR). From the Tensile Strength test, it can be concluded that the composite with 0.4wt % MWCNT was stronger than the sample without MWCNT. Due to its high mechanical strength and other unique properties, this Polyester composite has the potential to be used in various applications.